Respiratory Syncytial Virus - Nam, Hannah H.; Ison, Michael G. (Seminars in Respiratory and Critical Care Medicine, 2021)
Human respiratory syncytial virus (RSV) is a negative sense single-stranded RNA virus that can result in epidemics of seasonal respiratory infections. Generally, one of the two genotypes (A and B) predominates in a single season and alternate annually with regional variation. RSV is a known cause of disease and death at both extremes of ages in the pediatric and elderly, as well as immunocompromised populations. The clinical impact of RSV on the hospitalized adults has been recently clarified with the expanded use of multiplex molecular assays. Among adults, RSV can produce a wide range of clinical symptoms due to upper respiratory tract infections potentially leading to severe lower respiratory tract infections, as well as exacerbations of underlying cardiac and lung diseases. While supportive care is the mainstay of therapy, there are currently multiple therapeutic and preventative options under development.
Keywords: respiratory syncytial virus; ribavirin; palivizumab; presatovir; vaccine; pneumonia